The Review of ELC and STATCOM Role in Electrical Power Generation from Renewable Energy Sources Based Three-Phase Self-Excited Induction Generator - Melda Latif; Refdinal Nazir; Krismadinata Krismadinata (LPPM Universitas Andalas, 2026)
This paper reviews various control strategies employed in Electronic Load Controllers and Static Synchronous Compensators (STATCOMs) for renewable energy system (RES)-based Self-Excited Induction Generators (SEIGs), with particular emphasis on performance indicators such as voltage and frequency regulation, harmonic distortion mitigation, and dynamic response characteristics. The review was conducted using articles published in reputable scientific journals. A total of 52 articles were selected and analyzed based on predefined inclusion criteria. The findings indicate that the investigated control approaches range from conventional controllers, such as Proportional-Integral (PI) and Proportional-Integral-Derivative (PID) controllers, to intelligent control techniques, including Fuzzy Logic Controllers (FLCs) and Artificial Neural Networks (ANNs). Furthermore, hybrid control schemes, such as Fuzzy-PI controllers and optimization-assisted intelligent controllers (e.g., PI-PSO), have also been widely reported in the literature. The limitations of conventional PI/PID controllers, particularly their fixed gain parameters that are optimized for specific operating conditions, can be effectively addressed through intelligent control techniques. These advanced approaches provide improved adaptability, enhanced dynamic response, and superior harmonic compensation performance. As a result, the reported Total Harmonic Distortion values for both voltage and current are generally maintained within the limits specified by IEEE Standard 519, namely below 5% for both voltage THD and current THD.